In-company project: An integrated communication plan to increase the usage of the e-floater sharing service in Lisbon - Hofrichter, Jannick (2020)
This Master’s project is an in-company project about the micro mobility company Floatility that offers an electric micro scooter sharing service with its three-wheeled e-floater. The company figured out that most its e-floater trips were conducted by users who did three or more trips. In order to address these regular users and trigger more trips by them, it needs an effective integrated communication plan. As Floatility does not yet have a clear and structured communication plan for these regular users, the objective of this Master’s project is to develop an effective communication plan for the regular users of the e-floater sharing service in Lisbon. The users with the most trips during the three-month pilot project in Lisbon Carnide served as the target audience who were interviewed and surveyed in order to develop an integrated communication plan. Firstly, a situation analysis has been done incorporating the shared mobility market in Lisbon, Floatility’s competitors in Lisbon and the company’s efloater including its plans for the Lisbon market. Next, the integrated communication plan has been developed based on six steps proposed by Kotler and Armstrong (2012). They consist of identifying the target audience, determining the communication objectives, designing a message, choosing the right media, selecting the message source and collecting feedback from the users. Having analysed the results of the primary research with the regular users of the pilot project, eventually an implementation plan is recommended for Floatility’s operations in the entire city of Lisbon.